1993
DOI: 10.1002/cyto.990140215
|View full text |Cite
|
Sign up to set email alerts
|

Use of mouse hepatocytes for the flow cytometric determination of DNA levels of nuclei extracted from fresh tissue of hybrid larch (Larix × eurolepis Henry)

Abstract: A rapid and reliable method is presented to release intact nuclei from small amounts (100 mg) of fresh plant tissue. Further, an accurate and readily accessible new standard is proposed. Both techniques have potential application for many plant systems. The system chosen as a standard (inbred mouse strain Balb/ C or B6/AF1 hepatocyte nuclei) contains both diploid and polyploid cells. This system was applied in the flow cytometric determination of absolute nuclear DNA values of female gametophytes and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In order to estimate peak channel numbers for haploid and diploid tissue, nuclei isolated from megagametophyte tissue excised from dry seeds were passed on the same settings. A previous study (Wyman, Tremblay, and Laliberté, 1996) has shown that the majority of nuclei of gametophytic tissue from the dry seeds were in the 1C state. From this it was established that nuclei falling on the channel approximately twice this value contained DNA levels equivalent to the 2C state.…”
Section: Methodsmentioning
confidence: 89%
See 4 more Smart Citations
“…In order to estimate peak channel numbers for haploid and diploid tissue, nuclei isolated from megagametophyte tissue excised from dry seeds were passed on the same settings. A previous study (Wyman, Tremblay, and Laliberté, 1996) has shown that the majority of nuclei of gametophytic tissue from the dry seeds were in the 1C state. From this it was established that nuclei falling on the channel approximately twice this value contained DNA levels equivalent to the 2C state.…”
Section: Methodsmentioning
confidence: 89%
“…Thus, in order to compare embryos at the same physiological stage of germination the greening of embryos was taken into account. When we compared the percentage nuclei in the ''normal'' 2C-4C cell cycle between superior and inferior families, we noted that inferior families had significantly more nuclei ''blocked'' in the 2C state, although families begin imbibition with the same proportion of cells in the 2C state (Wyman, Tremblay, and Laliberté, 1996). After 144 h of imbibition this ''unblocking'' of the nuclei is greater in the families classified as superior.…”
Section: Dna Content Variation In Relation To Development-mentioning
confidence: 92%
See 3 more Smart Citations